2012
DOI: 10.1021/la302197z
|View full text |Cite
|
Sign up to set email alerts
|

Dye Bonding to TiO2: In Situ Attenuated Total Reflection Infrared Spectroscopy Study, Simulations, and Correlation with Dye-Sensitized Solar Cell Characteristics

Abstract: Processing dye-sensitized solar cells gains more and more importance as interest in industrial applications grows daily. For large-scale processing and optimizing manufacturing in terms of environmental acceptability as well as time and material saving, a detailed knowledge of certain process steps is crucial. In this paper we concentrate on the sensitizing step of production, i.e., the anchoring of the dye molecules onto the TiO(2) semiconductor. A vacuum-tight attentuated total reflection infrared (ATR-IR) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…For in situ ATR-IR experiments, a dedicated flow-through cell was used made from a Teflon piece and a fused silica plate (64 × 30 × 5 mm 3 ) with holes for inlet and outlet (39 mm apart) and a Viton seal (1 mm). The volume of the used flow-through cell is 0.129 mL with a gap of 270 μm . The cell was mounted on an attachment for ATR measurements within the sample compartment of the Fourier transform infrared (FTIR) spectrometer.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…For in situ ATR-IR experiments, a dedicated flow-through cell was used made from a Teflon piece and a fused silica plate (64 × 30 × 5 mm 3 ) with holes for inlet and outlet (39 mm apart) and a Viton seal (1 mm). The volume of the used flow-through cell is 0.129 mL with a gap of 270 μm . The cell was mounted on an attachment for ATR measurements within the sample compartment of the Fourier transform infrared (FTIR) spectrometer.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…The carboxylic acid group that anchors substituted porphyrin dyes to TiO 2 in the solar cells is known to be protonated in solution. 69 Protonated dyes were therefore initially analyzed in order to assess the different methodologies for the computational studies of the UV-vis spectra. The experimental reference data were reported by Kurotobi et al 22 The optimized geometry for the ZnPBAT molecule, studied in this work, is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A dedicated flow-through cell was used composed of a Teflon piece and a fused silica plate (45 × 35 × 3 mm) and the flow-rate was controlled by a peristaltic pump (Ismatec, Reglo 100) located before the cell. 50 A viton-ring seal (1 mm) defined the thickness of the fluid compartment, which had a volume of 0.5 mL. The cell was mounted on an attachment for ATR measurements (Wilks Scientific) within the sample compartment.…”
Section: Methodsmentioning
confidence: 99%